The Influence of Gender in Physics on Mastery of the Concept of Graph Representationthrough Test of Understanding Graphs in Kinematics (TUG-K) Analysis - Ahmad Ilmar; Sentot Kusairi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This study aims to determine the effect of gender on the mastery of the concept of graphical representation through the analysis of Test of Understanding Graphs in Kinematics (TUG-K). This research method is a comparative study that aims to compare two or more variables, to get answers or facts whether or not there is a comparison of the object being studied. This research is a qualitative research. The number of samples in this study were 23 people consisting of 8 male students and 15 female students. The research instrument used was 5 descriptive questions referred to from TUG-K Beichner and analyzed by the CRI method. Based on the results of the study, it was found that from the number of students who knew the concept, it was known that 1 out of 8 (1:8) male students knew the concept, and 3 out of 15 (1:5) female students. From this data, it can be seen that female students master concepts more than male students.